2003
DOI: 10.1023/a:1022564027468
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Recent studies have described a spasmolytic polypeptide-expressing metaplastic cell lineage (SPEM) in the gastric fundic mucosa associated with both chronic H. pylori infection and gastric adenocarcinoma. We investigated the association of SPEM both with early gastric adenocarcinoma and in biopsies taken from patients prior to diagnosis of cancer. Two cohorts were examined. First, gastric resections from 29 patients with early gastric cancer were examined. Second, biopsies taken from 18 patients prior to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…The observation of SPEM emerging rapidly after acute parietal cell loss induced by DMP777, L635 or high dose tamoxifen is consistent with this lineage performing a role in the response to injury [4143]. SPEM appears to resolve following resolution of injury and can often appear as a highly localized phenomenon [29,41,43]. Thus, acute ulceration injury in the stomach is associated with the appearance of SPEM around ulcers and SPEM contributes to the healing of these lesions [32,39,44].…”
Section: Spasmolytic Polypeptide-expressing Metaplasia (Spem)mentioning
confidence: 78%
See 1 more Smart Citation
“…The observation of SPEM emerging rapidly after acute parietal cell loss induced by DMP777, L635 or high dose tamoxifen is consistent with this lineage performing a role in the response to injury [4143]. SPEM appears to resolve following resolution of injury and can often appear as a highly localized phenomenon [29,41,43]. Thus, acute ulceration injury in the stomach is associated with the appearance of SPEM around ulcers and SPEM contributes to the healing of these lesions [32,39,44].…”
Section: Spasmolytic Polypeptide-expressing Metaplasia (Spem)mentioning
confidence: 78%
“…Spasmolytic polypeptide-expressing metaplasia (SPEM) was identified more than goblet cell-containing intestinal metaplasia in an initial cohort from the United States [28] and in association with early gastric cancers in Iceland [29]. This lineage showed many of the characteristics of deep antral gland cells or Brunner’s gland cells.…”
Section: Spasmolytic Polypeptide-expressing Metaplasia (Spem)mentioning
confidence: 99%
“…Recent studies have suggested that both SPEM and intestinal metaplasia may be pre-neoplastic metaplasias. In three separate studies, SPEM was associated with 90% of resected gastric cancers (23, 25, 29). TFF2 was also expressed in greater than 50% of early gastric cancers from Iceland (30).…”
Section: The Development Of Pre-neoplastic Metaplasia In the Stomachmentioning
confidence: 97%
“…In humans, two types of metaplasia arise in the milieue of oxyntic atrophy and inflammation: intestinal metaplasia and spasmolytic polypeptide expressing metaplasia (SPEM). Both intestinal metaplasia and SPEM have been associated with the progression to intestinal type gastric cancer (8, 1725). Thus, oxyntic atrophy in association with prominent inflammation incites the induction of gastric lineages that predispose to the development of gastric cancer.…”
Section: The Development Of Pre-neoplastic Metaplasia In the Stomachmentioning
confidence: 99%
“…Parietal cell atrophy causes increased proliferation of normal stem/progenitor cells in the isthmus (21). Clinically, the distributions of chronic parietal cell atrophy and SPEM have been associated with gastric cancer in 90% of resected stomachs (22,23), suggesting that SPEM could represent a surrogate marker of gastric cancer risk. However, the molecular mechanisms leading to SPEM and the expansion of progenitors in H. pylori-induced gastritis are largely unknown.…”
mentioning
confidence: 99%